THE EFFECT OF INCOME INEQUALITY AND POVERTY ON ECONOMIC GROWTH IN EAST LOMBOK DISTRICT - Lestari, Ayu; Yasin, Muaidy; Masrun, Masrun (Laboratorium Riset Ekonomi, 2024)
This study aims to determine the effect of income inequality and poverty on economic growth in East Lombok Regency. The research method used was associative quantitative to test the effect of income inequality and poverty on economic growth. The data used is secondary data obtained from the Central Statistics Agency (BPS) with the time period 2014-2023. The analysis technique used is multiple linear regression with the help of the e-Views 12 program. The results showed that the income inequality variable had a negative and insignificant effect on economic growth, while the poverty variable had a positive and significant effect on economic growth in East Lombok Regency.